STUDIES ON THE HISTOMORPHOMETRIC ANALYSIS OF REPRODUCTIVE ORGANS OF FIVE STRIPED SQUIRRELS (Funambulus pennanti) UNDER NATURAL ENVIRONMENTAL CONDITIONS - CHAUDHRY, ASIA MARYYAM; QURESHI, ANAS SARWAR; UL-HAASAN, MAHMOOD; DEEBA, FARRAH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
The present study was designed to investigate morphological and histometrical changes in the testes of five striped squirrels (Funambulus pennanti) in different breeding seasons. Sixteen specimens were collected from 3 different locations of Chiniot district, Punjab, Pakistan during different months to collect their testes samples. Body weight and external body measurements were recorded. Two adult males were euthanized and autopsied to obtain their male reproductive organs (i.e. testes, epididymis, penis) in intact form. Size and shape of reproductive organs were determined during three reproductive phases i.e quiescent phase (November), recrudescence phase (December) and peak reproductive phase (January to June). After euthanasia, the tests were excised washed with normal saline solution and fixed in Bouin’s solution, dehydrated, embedded in paraffin, cut into 5μm sections and stained with hematoxylin and eosin, for the examination under light microscopy. Statistical analysis revealed highly significant (P<0.05) values of all histological parameters of tests during the peaks spermatogenic phase in January-June when compared with the low spermatogenic phase in November and December. Significantly (P<0.05) higher values of testes parameters were observed during peak spermatogenic phase (January-June) as compared to others. Finally, this study shows that different stages of sexual activities are controlled by seasonal variations. These variations are according to different physical factors which influences anatomical and histological changes of testes and spermatogenesis of male five-striped northern palm squirrel (Funambulus pennanti) for adjustment in breeding phenology.